Implementation of the 5S program in the school environment: Challenges and opportunities (Research, Society and Development, 2020)
There are several challenges involving sustainable and reflective practices in school spaces. The implementation of the 5S program, founded after the Second World War, in Japan, proves to be a viable alternative for the creation of an organized school environment that promotes the construction of knowledge in sustainable ways. In this perspective, the present study aims to reflect on the importance of implementing the 5S program in educational environments. We present a study with a qualitative approach, and as for the procedures, it is bibliographic and documentary research. We show that the 5S quality program can promote significant improvements in the entire school environment, facilitating a change in the panorama in schools, to build collective knowledge in a meaningful way.